Enhanced B cell electroporation efficiency via inhibition of DNA-induced apoptosis and pyroptosis with pan-caspase inhibitor - Gui-Lin Yang; Deng-Gao Wang; Xiang Zhao; De-Long Hao; Zhu-Qin Zhang; De-Pei Liu (Molecular Therapy: Methods & Clinical Development)
B cells have immense potential as gene therapy carriers because of their ability to secrete therapeutic proteins and mediate immunological memory and tolerogenic functions. However, efficient gene delivery into primary B cells remains a challenge, as DNA electroporation frequently induces significant cell death. Here, we demonstrate that primary murine B cells undergo apoptosis and pyroptosis after DNA electroporation, which is driven primarily by activation of the cyclic GMP-AMP synthase stimulator of interferon genes (cGAS-STING) pathway in response to cytoplasmic double-stranded DNA (dsDNA). To overcome this, we pretreated B cells with a caspase inhibitor, which increased cell viability and improved DNA delivery and knock-in efficiency. Notably, compared with the inhibition of either apoptosis or pyroptosis alone, treatment with the pan-caspase inhibitor Boc-D-FMK resulted in a more significant improvement in cell viability and DNA electroporation efficiency. This approach significantly increased the expression and secretion of human erythropoietin (hEPO) both in vitro and in vivo. These findings not only elucidate the mechanisms underlying DNA-electroporation-induced cell death in B cells but also establish a strategy to optimize B-cell-based gene therapies and therapeutic protein production.